Analisis Inefisiensi Teknis Usaha Pertanian Padi Organik Dan Anorganik Di Kecamatan Kebakkramat Kabupaten Karanganyar - Cahyani, Agustin Lila; , Dr. Agung Riyardi, M.Si (2017)
This study entitled "Analysis of Technical Inefficiency Rice Farming Organic and Inorganic in District Kebakkramat Karanganyar". This study aimed to analyze the function of the agricultural production of rice and rice farming business technical inefficiency of organic and inorganic in the district of Karanganyar district Kebakkramat. Data used in this study are primary data in the form of data of land area, number of seeds, the number of manpower, jumlahpestisida, the amount of fertilizer, and the amount of production in the district of Karanganyar Kebakkramat. The analytical method used was Ordinary Least Square (OLS) method and Corrected Ordinary Least Squares (COLS) is the parametric approach, which is to analyze the functions of agricultural production of rice and technical inefficiency farming organic rice and organic with free variable influence (independent) on the dependent variable (dependent). The results of this study can be concluded that the test interpretation On the table looks R2 = 0.986047 means that 98.60% variable Total Production can be described independent variable land area, number of seeds, number of employees, number of pesticides, the amount of fertilizer in the statistical models and amounted to 0.0140 or 1.40%, the rest is explained by other variables that are not observed in the model. Technical inefficiency significant positive effect on total production Kebakkramat District of Karanganyar, with a total of 0.740. This means that if technical inefficiency rose by 1%, the total production will increase by 7.40%. Test Inefficiency of the technique used to find comparisons between organic fertilizer and inorganic fertilizer. Where the use of the more efficient fertilizer use. The results of these calculations, the value of organic fertilizer by 0.000308. Meanwhile, inorganic fertilizer value of 0.999. It can be concluded that the results of the analysis of the technical inefficiency of rice farming in the district Kebakkramat Karanganyar district, its farmers more organic than inorganic fertilizers and the result is more efficient.